Pengaruh Diameter Batang Bawah dan Hormon BAP (Benzyl Amino Purin) Terhadap Keberhasilan Sambung Pucuk Sawo - Nabila Nuraini Fatikhasari; Karno Karno; Budi Adi Kristanto (Universitas Sebelas Maret, 2021)
Sawo is a tropical native fruit from Indonesia, demand fot the fruit of sawo is increasing every year, one of the most effective ways to consumer demand is to vegetatif propagation that is top grafting. Top grafting can be accelerated by the addition of plant growth regulators. The purpose of this research was to know the success of top grafting of sawo plants at various sizes of diameter plant seedling and levels of BAP concentration. The method used was factorial complete randomized design with 2 factor,the first factor was diameter plant seedling (small, medium and big) and the second factor was concentrations of BAP (0, 100 and 200 ppm) with 5 replications. The result showed that diameter plant seedling small and medium gave a significant effect (P<0.05) on time of shoot, number of leaf and long of shoot. The levels of BAP concentration 100 and 200 ppm gave a significant effect on the time of shoot, number of shoot and long of shoot and percentage of success. There is interaction of diameter seedling and concentration of BAP against top grafting of sawo varieties jumbo vietnam.